The high-quality telomere-to-telomere genome assembly of the earthworm (Amynthas aspergillum) - Guangquan Peng; Yanghe Qin; Zhiming Yan; Mingwei He; Yucheng Zhao; Neng Jiang; Changhong Wei (Scientific Data)
Abstract Earthworms have been extensively studied as ancient soil invertebrates, that are highly diverse. Previous studies of these invertebrates have mainly focused on their ecosystem services, medicinal value, and ecological habits. However, their genomic analysis remains inadequate. In this study, we generated the first high-quality telomere-to-telomere (T2T) assembly of the genome of the earthworm, Amynthas aspergillum (Perrier, 1872), which belongs to the genus Amynthas of the family Megascolecidae. The T2T assembly was 758.86 Mb with an N50 contig size of 16.59 Mb. The sequences were anchored to 43 chromosomes (2n = 2x = 86) with a coverage of 98.43% (746.95 Mb), and 83 telomeres were detected. In addition, we also predicted 35,723 protein-coding genes with 97.02% being functionally annotated. This T2T genome assembly will establish substantial groundwork for exploring the evolutionary mechanisms of the earthworm genome and enhance the specificity of its pharmacological effects.